PWE-016 Faecal Calprotectin Has an Acceptable Sensitivity for Detecting Small Bowel Crohn's Disease: Results from Real World Clinical Practice. (17th August 2016) - Wu, J; Bolton, L; Chapman, C; Chey, CS; Harrison, E; Kinderman, H; Johnson, H; Richards-Taylor, A; Weaver, S; Mclaughlin, S
Abstract : Introduction: Faecal calprotectin 'FC' is a quick, non-invasive and inexpensive test proven to correlate well with colonic inflammation. It is used in our institution to also exclude active small bowel Crohn's disease 'CD' although its reliability in such cases has recently been questioned. Using a higher cut-off FC value may exclude active disease in those with known inflammatory bowel disease with a higher specificity and reduce the number of false positives. 1, 2 The aim of this study was to assess whether FC compared to gold standard magnetic resonance enterography 'MRE' can reliably be used in small bowel CD as a screening tool to select those needing further investigation. Methods: Data from all CD patients who had undergone MRE to assess for active small bowel CD between January 2012 to November 2015 were reviewed. Patients with a known or new diagnosis of ileal or ileo-caecal crohn's (Montreal classification L1 phenotype) or ileo-colonic crohn's (L3 phenotype) with endoscopic and histologically-proven quiescent colonic disease were included. Data was analysed using Mann-Whitney U testing. Results: 194 MREs were performed for investigation of possible small bowel CD during the study period. 64 patients were included for analysis; L1 disease = 90.6% (58 patients), L3 = 9.4% (6 patients). 50% were female. The median age was 48 years (range 17–76 years). Median time between FC and MRE was 30 days (range 0–180 days). 35 patients (54.7%) were Montreal disease behaviour B1, 24 patients (37.5%) with B2 and 5 patients (7.8%) with B3. 4 patients (6%) had peri-anal involvement. 26 patients (41%) had previous Crohn's-related resectional surgery. 39 patients (60.9%) had evidence of active small bowel CD at MRE. The median FC in the active CD group was 246 mg/kg (IQR 556) and 49 mg/kg for the inactive small bowel disease group (IQR 177.5); p < 0.0001. Table 1 shows results for sensitivity, specificity, positive predictive value 'PPV' and negative predictive value 'NPV' of different FC cut-off values in detecting any degree of small bowel activity at MRE. Conclusion: In this study we compared FC results to MRE to exclude or confirm active small bowel CD in real-world clinical practice. This data demonstrates that by using a cut-off value of 50 mg/kg, an acceptable sensitivity for detecting active small bowel CD is achievable. However, at this cut-off value, specificity is low; nevertheless using FC will still reduce demand for MRE. References: 1 F. Fascì-Spurio, A. Chiappini, V. Buonocore, S. Cannizzaro, Z. Maddalena, F. Maccioni, P. Vernia. (2014) Faecal calprotectin concentrations in Crohn's patients with ileal disease location: correlations with disease activity as seen by MRI enterography. European Crohn's and Colitis Organisation . 2 MF Hale, K Drew, ME McAlindon, AJ Lobo, R Sidhu. (2015). PTU-054 Faecal calprotectin in patients with suspected small bowel crohn's disease: correlation with small bowel capsule endoscopy. Gut 2015 ;64:A83. doi:10.1136/gutjnl-2015-309861.169 Disclosure of Interest: None Declared